2008
DOI: 10.1303/aez.2008.49
|View full text |Cite
|
Sign up to set email alerts
|

Different binding characteristics of dengue-2 virus to midgut of Aedes albopictus (Diptera: Culicidae) and Culex quinquefasciatus (Diptera: Culicidae)

Abstract: Radio binding assay and dot-virus protein binding assay were carried out to study the difference in binding of the brush border membrane fraction (BBMF) in Aedes albopictus (Skuse) and Culex quinquefasciatus (Say) (Diptera: Culicidae). The BBMF of Ae. albopictus displayed higher saturation and relative binding characteristics, while the BBMF of Cx. quinquefasciatus showed low saturation and non-relativity. The virus overlay protein-binding assay was then adopted to detect virus-binding protein in the midgut of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…quinquefasciatus midgut membrane using VOPBA. The findings of the present study therefore support the mesenteron infection barrier theory (Liu et al , ) from pathogenic and vector competence viewpoints.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…quinquefasciatus midgut membrane using VOPBA. The findings of the present study therefore support the mesenteron infection barrier theory (Liu et al , ) from pathogenic and vector competence viewpoints.…”
Section: Discussionsupporting
confidence: 91%
“…Culex quinquefasciatus is reported to be non‐permissive to dengue virus. Liu et al () demonstrated the absence of dengue virus (serotype 2) interacting proteins on Cx. quinquefasciatus midgut membrane using VOPBA.…”
Section: Discussionmentioning
confidence: 99%
“…However, less emphasis has been placed on understanding these interactions in non-competent mosquito species. Studies investigating these types of host-pathogen interactions have greatly informed our understanding of factors critical to vector competence (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%